TINGKAT KUALITAS KOTA DITINJAU BERDASARKAN KEBUTUHAN LUASAN RUANG TERBUKA HIJAU DI KOTA DEPOK - Sulastri, Mila; AT, Mulyadi; Arifien, Yunus (Jurnal Nusa Sylva, 2013)
In a way, the city experienced rapid growth due to population dynamics, socioeconomic change, and from the interaction with the other regions. Population growth resulted in the densification of population and settlements rapid and uncontrolled in that part of town. The increasing demand for specialized space for resettlement and land up to the growing impact of environmental quality deterioration. Spatial Plan that was created was not able to prevent urban land conversion so that the presence of green open space (RTH) is threatened and the city is not pleasant to be around. The main problem is the reduction in the presence of RTH RTH due to limited land and inconsistent in applying the spatial. RTH is caused by a reduction in the conversion RTH function switch to another space allotment.According to Law no. 26 of 2007 of the act states that the proportion of green space of at least 30% of the area of the city. Urban green space consists of RTH Public Private dn, where the proportion of public green space is 20% and for RTH Privat is 10%. But the facts on the ground stated that the presence of green space that is far from ideal proportions, the dominant market power of changing land use so that the presence of green space terpingirkan even neglected its function and purpose. Development in urban areas continue to be implemented, see Depok as a buffer for the city which is the center of the capital Jakarta. Currently Depok City Government with the whole community is in it until the end of 2012, has fulfilled its obligation to build one of 3110.88 ha (15.48% of the area of the city of Depok) green open space in the city of Depok consisting RTH an area of 1855.15 hectares of public green space and an area of 1255.73 ha Privat.